Effects of Aerobic Exercise and Yoga Breathing Exercise (Pranayama) on Blood Pressure in Hypertensive Patients - Khairunissa Khairunissa; Didik Gunawan Tamtomo; Hanung Prasetya (Journal of Epidemiology and Public Health, 2021)
Background: Uncontrolled hypertension or high blood pressure is a major risk factor for cardiovascular disease. Non-pharmacological treatment has become an important part of hypertension management. Aerobic exercise and yoga breathing exercise (pranayama) are types of non-pharmacological treatment that have an effect on lowering blood pressure. This study aims to examine the effect of aerobic exercise and yoga breathing exercise (prana